353. Implementation of a dose data collection software system: structure of data and CT preliminary results. (December 2018) - Bellesi, L.; Wyttenbach, R.; Gaudino, D.; Pupillo, F.; Ramundo, M.; Piliero, M.A.; Casiraghi, M.; Gerbino, M.; Mascaro, F.; Presilla, S.
Abstract : Purpose: CT protocols review and optimization require a considerable amount of time and dedicated staff especially to compare dose levels among multicentre institutions and with national and international average values. The purpose of this article is to describe the structure of data collection for a dose radiation tracking software used to analyse a large amount of CT dose data. This should be done in order to audit scanner protocols, improve staff and patient safety and optimize all the diagnostic workflow. Methods: The software implementation team included a team leader, two radiology technologists, two medical physicists and the chief of radiology department. Very detailed data collection folders and diagnostic reference values (DRV) were created based on 25th percentile, as target value, and 75th percentile, as upper limit, values of CTDIvol and DLP extracted from Swiss CT DRV. Data were collected from seven different multislice CT scanners using the study description Dicom tag. Results: Direct protocol comparison, for each institution/scanner, is presented. About 90% of CT exams applied a dose inferior to Swiss DRV. Conclusions: DVRs represent a benchmark useful to optimize radiation dose. Multisite cross-analysis of CT protocols allows the adoption of the best dose-optimized protocols in each center. Outliers and dose reduction strategies are discussed periodically within a team meeting: analyses are performed using a Montecarlo simulation tool to optimize future exams by varying setup parameters and study length. On request, total effective and individual organ dose values, are available especially for pregnant patients immediately after diagnostic examinations[1, 2] .